Cryptoasset ownership and use in Canada: An update for 2022 - Daniela Balutel; Christopher S. Henry; Doina Rusu (Bank of Canada, 2023)
This paper provides an update on cryptoasset ownership in Canada using data from two Bank of Canada surveys conducted in 2022. We find that Bitcoin ownership declined from 13% in 2021 to 10% in 2022, and ownership of other cryptoassets also fell. These drops occurred against a background of steep price declines and an increasingly tight regulatory atmosphere for cryptoassets.
Keywords: E4; C81; O51; 330; Bank notes; Digital currencies and fintech; Econometric and statistical methods